2018
DOI: 10.15275/rusomj.2018.0306
|View full text |Cite
|
Sign up to set email alerts
|

Lung function and respiratory symptoms among mine workers in the Eastern part of Iran

Abstract: Background -Workers in the mineral industries are exposed to airborne dust and its occupational exposure can cause respiratory disorders. The aim of this study was to determine the lung function and respiratory symptoms of workers exposed to mineral dust in the Eastern part of Iran. Material and Methods -This cross-sectional study was conducted on 156 workers in kaolin mine, gold mine, quarry, and stone cutting workshops as a dust exposed group and 48 administrative personnel in these sections as an unexposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
2
5
1
Order By: Relevance
“…Employees who had work experience of 6–9 years and ≥10 years were significantly associated with chronic respiratory symptoms. This result was consistent with the studies conducted in Iraq and Egypt [ 19 , 20 ]. This might be due to the increased amount of dust retention in respiratory system associated with extended exposure at work places.…”
Section: Discussionsupporting
confidence: 93%
“…Employees who had work experience of 6–9 years and ≥10 years were significantly associated with chronic respiratory symptoms. This result was consistent with the studies conducted in Iraq and Egypt [ 19 , 20 ]. This might be due to the increased amount of dust retention in respiratory system associated with extended exposure at work places.…”
Section: Discussionsupporting
confidence: 93%
“…37 The spirometry values (FVC%, FEV 1 ) were statistically significant (p < 0.01) and had similar differences between the control group and marble workers to our study. Furthermore, many previous studies in India, 38 Thailand, 39 Iran, 40 Egypt, 41 Nigeria, 15 and Libya 16 reported similar findings and mean values of pulmonary function parameters were found to be remarkably deteriorated resulting in pulmonary dysfunction.…”
Section: Discussionsupporting
confidence: 56%
“…A comparison was made among 156 workers in kaolin mine, quarry, gold mine, and stone cutting workshops (considered the dust-exposed group) and 48 administrative personnel (considered the unexposed group) in Eastern, Iran. The results revealed considerably lower PFT values in the exposed groups ( 90 ).…”
Section: Resultsmentioning
confidence: 88%